Avaliação in vitro da suscetibilidade antifúngica de conídios e células muriformes de Fonsecaeae spp - TAKAHASHI, Aline Barral (2018)
Chromoblastomycosis (CBM) is a fungal disease characterized by chronic cutaneous and subcutaneous lesions, due to the previous transcutaneous implantation of different black fungi, belonging to the family Herpotrichiellaceae, the main agent belonging to the genus Fonsecaea. The Amazon region is the main endemic area of Brazil and our state is the main endemic area in the country and second in the world. There is no standardization of treatment, drug therapy is used, with different regimens, mainly itraconazole. New azolics such as posaconazole and voriconazole began to be used, but with limitations due to the high cost, the use of physical methods such as cryosurgery, thermotherapy, laser therapy and both. The low cure rates and high rates of relapse of the disease may be related to the different treatment methods employed and the lack of a standardized regimen itself. The objective of this work was to evaluate the in vitro sensitivity of conidia and in vitro induced muriform cells of Fonsecaea spp. in the presence of different antifungal agents, to date there are no studies evaluating the action of drugs using the pathogenic form of the fungus, reinforcing the importance of this study, following the method established in the standard M38-A2, Clinical and Laboratory Standards Institute. The minimum inhibitory concentration for each drug was obtained after 5 days of interaction, posaconazole showed better in vitro inhibitory activity for conidia (CIMMG = 0.632μg / ml) and muriform cells (CIMMG = 1μg / ml). In the analysis of the fungicidal concentration, in both conidia and muriform cells, posaconazole presented lower value (CFMMG = 6.72μg / ml, in both). The fungus samples presented distinct times to differentiate their conidia in muriform cells, therefore we believe that although they belong to the same genus the fungi present physiological peculiarities still unknown. In the in vitro susceptibility tests PCZ had the lowest inhibitory and fungicidal concentrations in both conidia and muriform cells, thus investing in susceptibility testing was important to identify sensitive or resistant strains.